2015
DOI: 10.13075/ijomeh.1896.00460
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin exposure and changes in short-term pulmonary function among sewage workers

Abstract: Objectives:The inhaled endotoxin is considered as a causative factor in the process of acute bronchial obstruction, which can be measured by a decrease in forced expiratory volume in 1 s (FEV 1 ). The aim of this study was to assess endotoxin exposure among sewage treatment plant workers (STPW) and its effect on across-shift changes in respiratory airflow. Material and Methods: A group of 78 STPW from a large sewage treatment plant was studied. Inhalable dust for endotoxin assessment was collected using person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…In turn, changes in lung function of individuals exposed to dogs were not associated with atopy. It has been shown that households in which there are dogs have greater levels of airborne endotoxins ( 12 ) and exposure to endotoxins may worsen lung function ( 13 , 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…In turn, changes in lung function of individuals exposed to dogs were not associated with atopy. It has been shown that households in which there are dogs have greater levels of airborne endotoxins ( 12 ) and exposure to endotoxins may worsen lung function ( 13 , 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Endotoxins have been considered to be one of the main factors contributing to occupational lung diseases and organic dust toxic syndrome (Park et al, 2015). In fact, changes in pulmonary function due to endotoxin exposure have been (Paudyal et al, 2011), dairy workers (GM: 329 EU/m 3 (Mitchell et al, 2015), animal feed and grain workers (GM: 662 EU/m 3 ), and sewage treatment plant workers (GM: 214 EU/m 3 ) (Cyprowski et al, 2015).…”
Section: Endotoxinsmentioning
confidence: 99%
“…The airborne concentrations of endotoxin detected were at or below the range of concentrations reported in published studies. Endotoxin concentrations reported for sewage treatment workers in published studies ranged from 0.7 EU/m 3 to 214 EU/m 3 [Cyprowski et al 2015]; ND to 1630 EU/m 3 [Krajewski et al 2004]; 38 EU/m 3 to 322, 000 EU/m 3 [Rylander 1999]; and 0.6 EU/m 3 to 2093 EU/m 3 [Smit et al 2005]. The area air sampling results for endotoxin collected in two locations (near the bag loading of the final product and at the end of the thermal drying machine) were not detectable at a minimum detectable concentration of 1 EU/m 3 .…”
Section: Environmental Assessment Air Samplingmentioning
confidence: 99%
“…Endotoxin exposure has also been associated with skin itch and rash [Manfreda et al 1986], but these associations have not been well documented. Endotoxin exposures have been associated with decreased lung function and airway inflammation with sewage workers [Cyprowski et al 2015]. Although scientists agree that endotoxins can cause human health effects, no universally accepted OELs have been developed because of the variability in sampling and analytical methods and a lack of data showing a consistent dose-response relationship [Paba et al 2013].…”
Section: Endotoxinmentioning
confidence: 99%